SISTEM INFORMASI PEMESANAN HANDPHONE SECOND PADA STORE AS GADGET BERBASIS WEB MENGGUNAKAN SMS GATEWAY - Hasanah, Nia Aswatul; Candra, Adi; Nur, Muhammad Awal (journal Informatika, Multimedia, dan Informasi, 2024)
Research has been to design a second handphone ordering information system on as gadget store based on website using SMS Gateway and to implement second handphone ordering information system on as gadget store based on website using SMS Gateway. The method used is the waterfall method is a model that provides systematic and sequential approaches for software developers, namely Requirement Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance, in designing the system using unified modeling language (UML), namely use case diagrams, activity diagrams and sequence diagrams, programming languages used PHP, MySQL as database storage, SMS Gateway as a liaison between the application or system with a mobile phone and testing is done using the black box method. The results of the study showed that this application can be used easily by its users based on the average result of SUS which is 70.3 which means it has a Grade Scale B and is included in The Good category.